Nod2: A Critical Regulator of Ileal Microbiota and Crohn’s Disease - Sidiq, Tabasum; Yoshihama, Sayuri; Downs, Isaac; Kobayashi, Koichi S. (Frontiers in Immunology, 2016)
The human intestinal tract harbors large bacterial community consisting of commensal, symbiotic and pathogenic strains, which are constantly interacting with the intestinal immune system. This interaction elicits a non-pathological basal level of immune responses and contributes to shaping both the intestinal immune system and bacterial community. Recent studies on human microbiota are revealing the critical role of intestinal bacterial community in the pathogenesis of both systemic and intestinal diseases including Crohn’s disease (CD). NOD2 plays a key role in the regulation of microbiota in the small intestine. NOD2 is highly expressed in ileal Paneth cells that provide critical mechanism for the regulation of ileal microbiota through the secretion of anti-bacterial compounds. Genome mapping of CD patients revealed that loss of function mutations in NOD2 are associated with ileal CD. Genome-wide association studies (GWAS) further demonstrated that NOD2 is one of the most critical genetic factor linked to ileal CD. The bacterial community in the ileum is indeed dysregulated in Nod2-deficient mice. Nod2-deficient ileal epithelia exhibit impaired ability of killing bacteria. Thus, altered interactions between ileal microbiota and mucosal immunity through NOD2 mutations play significant roles in the disease susceptibility and pathogenesis in CD patients, thereby depicting NOD2 as a critical regulator of ileal microbiota and Crohn’s disease.